Oral creatine supplementation and short-term dynamic power production in healthy young men - Flanagan, E. P.; Jakeman, P. M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This experiment examined the effect of creatine monohydrate supplementation on corrected peak power output and peak acceleration during repeated, high intensity sprint cycling. The investigation was randomised, placebo-controlled, double-blind and adopted a crossover design. Eight male, adult volunteers participated in this study. Subjects were administered with creatine monohydrate (0.28g.kg-1 per day) or a glucose placebo. Following experimental treatments, subjects underwent 10 maximal effort, 6-s sprints on a cycle ergometer with a work to rest ratio of 5:1. The exercise protocol was fatiguing in nature with peak power output and peak acceleration decreasing significantly from the first to last sprint. Creatine supplementation significantly attenuated the decline in peak power output in the latter stages of the intermittent sprint cycling.